Lower vs higher transfusion threshold in septic shock patients of different ages: A study protocol. Issue 9 (21st July 2019) - Jonsson, Andreas Bender; Granholm, Anders; Rygård, Sofie Louise; Holst, Lars Broksø; Møller, Morten Hylander; Perner, Anders
Abstract : Background: Current evidence indicates that it is safe to use a lower haemoglobin (Hb) threshold for red blood cell (RBC) transfusion as compared to a higher Hb‐threshold. However, the recent Transfusion Requirements in Cardiac Surgery (TRICS‐3) trial reported a significant interaction between patient age and the effect of lower vs higher Hb‐thresholds for RBC transfusion. The interaction between patient age and transfusion strategy appears to differ between trials. Methods: This is the protocol and statistical analysis plan for a post hoc analysis of the Transfusion Requirements in Septic Shock (TRISS) trial. We will assess the effect of a lower vs a higher Hb‐threshold for RBC transfusion in patients of different ages with septic shock. The primary and secondary outcomes are 1‐year mortality and 90‐day mortality respectively. We will assess age divided into six age groups and as a continuous variable and present baseline characteristics and odds ratios derived from both simple and adjusted (for the Sequential Organ Failure Assessment score, haematological malignancy, age and trial site) logistic regression models and P ‐values for the test‐of‐interaction. Furthermore, we will compare outcomes according to Hb‐threshold in each age group using Kaplan‐Meier curves and log‐rank tests. Discussion: The outlined study will make a detailed assessment of potential interaction of patient age with transfusion strategy in patients with septic shock. This may inform future trials on the benefits and harms of RBC transfusion.